Walking training with cueing of cadence improves walking speed and stride length after stroke more than walking training alone: A systematic review - Nascimento L.R. (2015)
© 2014 Australian Physiotherapy Association.Question: After stroke, is walking training with cueing of cadence superior to walking training alone in improving walking speed, stride length, cadence and symmetry? Design: Systematic review with meta-analysis of randomised or controlled trials. Participants: Adults who have had a stroke. Intervention: Walking training with cueing of cadence. Outcome measures: Four walking outcomes were of interest: walking speed, stride length, cadence and symmetry. Results: This review included seven trials involving 211 participants. Because one trial caused substantial statistical heterogeneity, meta-analyses were conducted with and without this trial. Walking training with cueing of cadence improved walking speed by 0.23 m/s (95% CI 0.18 to 0.27, I2=0%), stride length by 0.21 m (95% CI 0.14 to 0.28, I2=18%), cadence by 19 steps/minute (95% CI 14 to 23, I2=40%), and symmetry by 15% (95% CI 3 to 26, random effects) more than walking training alone. Conclusions: This review provides evidence that walking training with cueing of cadence improves walking speed and stride length more than walking training alone. It may also produce benefits in terms of cadence and symmetry of walking. The evidence appears strong enough to recommend the addition of 30minutes of cueing of cadence to walking training, four times a week for 4 weeks, in order to improve walking in moderately disabled individuals with stroke. Review Registration: PROSPERO (CRD42013005873). [Nascimento LR, de Oliveira CQ, Ada L, Michaelsen SM, Teixeira-Salmela LF (2015) Walking training with cueing of cadence improves walking speed and stride length after stroke more than walking training alone: a systematic review.